A socio-technical critique of tiered services: implications for interprofessional care. Issue 1 (January 2015) - Hood, Rick
Abstract In the health and social care sector, tiered services have become an increasingly influential way of organising professional expertise to address the needs of vulnerable people. Drawing on its application to UK child welfare services, this paper discusses the merits of the tiered model from a socio-technical perspective – an approach that has emerged from the fields of accident analysis and systems design. The main elements of a socio-technical critique are outlined and used to explore how tiered services provide support to families and prevent harm to children. Attention is drawn to the distribution of expertise and resources in a tiered system, and to the role of referral and gate-keeping procedures in dispersing accountability for outcomes. An argument is made for designing systems "against demand", and the paper concludes by discussing some alternative models of multi-agency provision.